Numerical simulations and analysis of the turbulent flow field in a practical gas turbine engine combustor. (June 2022) - Hasti, Veeraraghava R; Kundu, Prithwish; Som, Sibendu; Gore, Jay P
The turbulent flow field in a practical gas turbine combustor is very complex because of the interactions between various flows resulting from components like multiple types of swirlers, dilution holes, and liner effusion cooling holes. Numerical simulations of flows in such complex combustor configurations are challenging. The challenges result from (a) the complexities of the interfaces between multiple three-dimensional shear layers, (b) the need for proper treatment of a large number of tiny effusion holes with multiple angles, and (c) the requirements for fast turnaround times in support of engineering design optimization. Both the Reynolds averaged Navier–Stokes simulation (RANS) and the large eddy simulation (LES) for the practical combustor geometry are considered. An autonomous meshing using the cut-cell Cartesian method and adaptive mesh refinement (AMR) is demonstrated for the first time to simulate the flow in a practical combustor geometry. The numerical studies include a set of computations of flows under a prescribed pressure drop across the passage of interest and another set of computations with all passages open with a specified total flow rate at the plenum inlet and the pressure at the exit. For both sets, the results of the RANS and the LES flow computations agree with each other and with the corresponding measurements. The results from the high-resolution LES simulations are utilized to gain fundamental insights into the complex turbulent flow field by examining the profiles of the velocity, the vorticity, and the turbulent kinetic energy. The dynamics of the turbulent structures are well captured in the results of the LES simulations.